Evaluation of Urban Road Stability Through the Integration of the Surface Distress Index and International Roughness Index - Oktopianto, Yogi; Antonius, Antonius; Rochim, Abdul (Jurnal Fondasi, 2025)
In an effort to improve the quality of transportation infrastructure, road maintenance requires an evaluation of road conditions. The Surface Distress Index (SDI) and the International Roughness Index (IRI) are two primary classical indicators used to assess road conditions. Although both are utilized independently, the relationship between them has not been widely studied. This research aims to analyze the correlation between the Surface Distress Index (SDI) and the International Roughness Index (IRI), particularly in the context of road maintenance, and to evaluate the effectiveness of integrating both indices in urban road maintenance planning. This study was conducted using a correlation method and approach, involving field data collection along urban road segments. The SDI and IRI were measured using standard measurement devices provided by Bina Marga, and the correlation patterns between the two were analyzed statistically. The findings reveal that SDI is significantly correlated with IRI, indicating that as surface distress (SDI) increases, it directly leads to an increase in road surface roughness (IRI). The results also indicate that combining the two indices can improve the accuracy of road condition assessments. The quadratic model was identified as the most optimal for describing the relationship between SDI and IRI, with a model performance explaining 79% of the variation in IRI.